Teaching Laminar-flow reactors: From experimentation to CFD simulation - L. M. Madeira (2006)
An integrated chemical engineering lab experiment is described in this paper. It makes use of a laminar-flow tubular reactor (LFTR) through consecutive lab sessions. In a first session (not described here), the pseudo first-order kinetic constant for the reaction between crystal violet and sodium hydroxide is determined at different temperatures in a batch reactor. Then a tracer experiment is used to characterize the flow, pattern in the LFTR, and finally the steady-state conversion of crystal violet in the reactor is measured. For computing the theoretical reactor conversion, students must use the previously collected kinetic and tracer data, in a concept-integration exercise. A computational fluid dynamics (CFD) code (Fluent) is also used to simulate both the tracer and the isothermal reaction experiments performed in the LFTR. A very good agreement is obtained between experimental and simulated results and both only differ slightly from the theoretical predictions. The use of the CFD program is particularly noteworthy. For instance, transient simulations allow a very nice visualization of the tracer concentration front evolution, while the steady-state profiles along the axial position provide a good perspective of how reactant concentration varies within the reactor.